2022
DOI: 10.15244/pjoes/143579
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution Characteristics of Rainstorm and Flood Disasters Around Tarim Basin

Abstract: The Tarim Basin is highly vulnerable to rainstorm and flood disasters, related to its special position of C-shaped terrain in the westerly belt and the ever-present monsoons. According to data of the storms and floods that occurred near the Tarim Basin from 1980 to 2019, the proportional weight method was used to construct the disaster exponent; whereas, the percentile method was used for classification. As a result, the disaster level is divided into four grades: mild, moderate, severe, and extremely severe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In order to compare the strength of disaster events, it is necessary to construct an actual disaster damage exponent (Ζ ) that can comprehensively express the five disaster factors. The weight of each disaster element was determined by the ratio method, and then the dimensionless linear combination method was used to obtain Ζ [24,25]. Suppose that each disaster factor consists of Ν sample, Ν=1394, so the disaster factor evaluation matrix Χ can be obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare the strength of disaster events, it is necessary to construct an actual disaster damage exponent (Ζ ) that can comprehensively express the five disaster factors. The weight of each disaster element was determined by the ratio method, and then the dimensionless linear combination method was used to obtain Ζ [24,25]. Suppose that each disaster factor consists of Ν sample, Ν=1394, so the disaster factor evaluation matrix Χ can be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In 38 counties (cities) in Northern Xinjiang, from 1981 to 2019, the frequency and intensity of flood disasters showed obvious regional differences. And the cumulative number of disasters that occurred on average over these 39 years in each region was as follows: Boltala Mongolian Autonomous Prefecture (70), Altay region (47), Yili Valley (45), northern Tianshan Mountains (25), Tacheng Area (21), which showed that the disaster events occurred most in Bortala Mongolian Autonomous Prefecture, and the least occurred in Tacheng Area; among them, Wenquan County had the most flood disasters, with a total of 103 occurrences (Figure 2a). Regional average annual damage exponents were as follows: Yili Valley (2.354), Altay (0.819), Tcheng (0.450), northern Tianshan (0.384), Bortala Mongolian Autonomous Prefecture (0.379).…”
Section: Spatial Distribution Of Flood Disaster In Northern Xinjiangmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with global warming, the frequency and intensity of extreme precipitation events have increased. In 2020, rainfall in the Yangtze River basin will reach 1441.5 mm, 22% more than usual and the most since 1961 (Chen, 2020;Huang et al, 2021). Under the influence of heavy rain in the middle and lower reaches of the Yangtze River, Poyang Lake experienced a large-scale flood.…”
Section: Introductionmentioning
confidence: 99%
“…Torrential flooding refers to the disasters caused by torrential rains or long-time heavy rainfalls, such as mountain torrents, debris flows and urban waterlogging [1]. Torrential flooding is one of the most frequent and serious natural disasters in China, causing huge economic losses and casualties every year [2,3].…”
Section: Introductionmentioning
confidence: 99%